Interworking DSRC and 5G cellular technologies for vehicle-to-everything communication - Siah, Cheon Kee (Nanyang Technological University, 2021)
Vehicle-to-Everything communication (V2X) is an application of wireless technology. It allows the communication between various entities, such as vehicles, pedestrians, networks, and infrastructure. As technology advances happen on a day-to-day basis, V2X has expanded to the usage of cellular technologies for its communication. As such, V2X employs two different technology methods for communication, Dedicated Short-Range Communication (DSRC) and the new Cellular Vehicle to Everything(C-V2X) technology. These two technologies are designed to support the different applications covered by V2X communication, such as obstacle avoidance, hazard warning systems, electronic payments, etc. Both technologies of the V2X broadcasts messages from the Transmitter (Tx) to Receiver (Rx). Within the message sets of the two technologies lies an important message set, the Basic Safety Message (BSM). This message set contains critical information about the transmitting vehicle. As such, high success receiving rates are required for the Rx to properly assess the situation around it. During wireless transmissions, devices may cause interference with one another when broadcasting on nearby wavelengths. Studies have shown that signal degradation is common when multiple devices of nearby wavelengths are broadcasting their messages at the same time. This wireless transmission characteristic is not excluded for V2X technologies. As such, C-V2X and DSRC messages may collide with one another, causing high packet loss. This would result in poor reaction time during V2X applications, leading to delayed reaction times for drivers and pedestrians. This report aims to explore the impacts of adjacent channel interference through the use of Packet Delivery Ratio (PDR) measurements using Line-of-Sight (LOS) and Non-Line-of-Sight (NLOS) experiments.